Gamma Radiation Effect on Commercial Reactive Dye in the Range 0-100KGy Using the Idea of the De-Coloration Factor and Extinction Coefficient. - Taqmeem Hussain; Muhammad Attique Khan Shahid; Muhammad Shahbaz; Inam-ul-Haq; Hashim Farooq (Journal of Basic & Applied Sciences, 2012)
In this study the usability of aqueous solutions of SR C4BLN and SGY CRL dyes; as secondary dosimeter was checked using the novel idea of de-coloration factor and extinction coefficient. All samples were irradiated by Co60γ-source in the range 0-105Gy. Absorbance of solutions was noted at λmax for pre and post irradiation stages. The λmax of Red and Yellow dyes were 545nm and 448nm respectively. The absorbance%, extinction coefficient and %age of de-coloration factor for each dye were determined. The results showed a gradual decrease in Absorbance% and extinction coefficient while decrease in %age of de-coloration factor with the increase in absorbed dose which confirms the said dyes as secondary dosimeter in stable and safe mode.